Determinants of The Prevention of Mother-to-Child Transmission of HIV/AIDS In Jombang Regency - Rodiyah, Rodiyah; Andayani, Sestu Retno Dwi; Syarifah, Anis Satus (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
The prevention of mother-to-child transmission (PMTCT) of HIV remains a major public health challenge in Indonesia, particularly in regions where stigma, limited knowledge, and weak social support hinder optimal program implementation. This study aimed to identify determinants influencing PMTCT efforts among HIV-positive pregnant women in Jombang Regency. An analytical observational design with a cross-sectional approach was employed, involving 30 pregnant women selected through systematic sampling. Data were collected using structured questionnaires and analyzed with univariate and bivariate methods using Spearman-Rho correlation. The results showed that 60% of respondents demonstrated adequate prevention efforts, while 40% were inadequate. Attitude (p = 0.006), parity (p = 0.010), peer support (p = 0.000), husband support (p = 0.010), healthcare worker support (p = 0.010), and accessibility (p = 0.028) were significantly associated with prevention behaviors. Peer support emerged as the strongest determinant, reflecting the importance of social networks and interpersonal influences. The findings indicate that PMTCT success requires more than clinical interventions; it depends on strengthening social support systems, improving counseling quality, and enhancing access to maternal health services. Integrated, community-based strategies are essential for reducing HIV transmission and achieving PMTCT targets.